Intensive care unit physician-delivered point of care renal tract ultrasound in acute kidney injury is feasible. (November 2018) - Parulekar, Prashant; Neil-Gallacher, Ed; Harrison, Alex
Acute kidney injury is common in critically ill patients, with ultrasound recommended to exclude renal tract obstruction. Intensive care unit clinicians are skilled in acquiring and interpreting ultrasound examinations. Intensive Care Medicine Trainees wish to learn renal tract ultrasound. We sought to demonstrate that intensive care unit clinicians can competently perform renal tract ultrasound on critically ill patients. Thirty patients with acute kidney injury were scanned by two intensive care unit physicians using a standard intensive care unit ultrasound machine. The archived images were reviewed by a Radiologist for adequacy and diagnostic quality. In 28 of 30 patients both kidneys were identified. Adequate archived images of both kidneys each in two planes were possible in 23 of 30 patients. The commonest reason for failure was dressings and drains from abdominal surgery. Only one patient had hydronephrosis. Our results suggest that intensive care unit clinicians can provide focussed renal tract ultrasound. The low incidence of hydronephrosis has implications for delivering the Core Ultrasound in Intensive Care competencies.